Effect of varying level of palm kernel cake (PKC) on growth performance, carcass composition and meat quality of Cherry Valley duck - Zulkipli, Mohamad Arif (2015)
Duck is another source of protein for the human consumption come from poultry industry. Because of the increase in human population, the demand for the duck meat are also increase instead of broiler meat. Palm Kernel Cake (PKC) is the agro industrial by-product form the oil palm plantation which is abundance in amount and can be easily get from the mill. PKC is a cost effective, cheap and a practical ingredient to be utilized in ration formulation for various livestock species. PKC is considered as a moderate protein feed, this is because PKC contain about 16 to 18% crude protein which met the need of requirement of certain classes of poultry. Taking this as an opportunity, a study was conducted using 36 male of Cherry Valley duckling and reared until 56 days of age. The duckling were fed a standard duck commercial diet for 14 days. At 14 days of age, they were divided randomly into three treatment groups. Each treatment had three replicate which contain four duckling per replicate. The dietary treatments were T1 (control), T2 (basal diet + 15% PKC) and T3 (basal diet + 35% PKC) respectively. The experimental diets were isocaloric and isonitrogenous calculated and were formulated to meet the minimum requirements of the National Research Council (NRC).Body weight, feed intake, weight gain and feed/gain were recorded every week. Body weight was measured individually, while feed intake was determined on group basis. After 56 days, one duck from each replicate of treatment was subjected to carcass composition and the remaining of the duck was subjected to the meat quality. Result shows that there were no significance difference (p>0.05) of body weight and weight gain of the T2 and T3 when compare to the T1. Significance different (p<0.05) for feed intake of T3 when compared to the T1 but T2 show no significant difference (p>0.05) when compare with T1. For the feed conversion ratio (FCR), there was significance different (p<0.05) for T3 when compared to the T1 but no significance different (p>0.05) for T2 when compare to the T1. For meat quality and dressing percentage, there were no significant different (p>0.05) for meat quality and dressing percentage of T2 and T3 when compared to the T1. No significant different (p>0.05) observed on the organ proportion, liver and heart when compared to the T1. However, significant different (p<0.05) was noted for gizzard of T2 and T3 when compared to the T1. From this study, it can be conclude that the inclusion of T2 (15%PKC) was recommended for duck feeding because it has no significant different in terms of growth performance, carcass composition and meat quality when compared to the T1.